Interpolation of the schwarzschild and Bertotti-Robinson solutions - Halilsoy, Mustafa (General Relativity and Gravitation, Springer, 1993)
The two well-known solutions of general relativity, the Schwarzschild and the Bertotti-Robinson solutions, are shown to be described by a common metric. In a particular coordinate system we show the connection between this metric and the metric of Reissner-Nordström.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1007/BF00756262) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Bertotti-Robinson; Reissner-Nordström; Schwarzschild; general relativity